Fighting cytokine storm and immunomodulatory deficiency: By using natural products therapy up to now - Mona A. Mohammed (Frontiers Media S.A., 2023)
A novel coronavirus strain (COVID-19) caused severe illness and mortality worldwide from 31 December 2019 to 21 March 2023. As of this writing, 761,071,826 million cases have been diagnosed worldwide, with 6,879,677 million deaths accorded by WHO organization and has spread to 228 countries. The number of deaths is closely connected to the growth of innate immune cells in the lungs, mainly macrophages, which generate inflammatory cytokines (especially IL-6 and IL-1β) that induce "cytokine storm syndrome" (CSS), multi-organ failure, and death. We focus on promising natural products and their biologically active chemical constituents as potential phytopharmaceuticals that target virus-induced pro-inflammatory cytokines. Successful therapy for this condition is currently rare, and the introduction of an effective vaccine might take months. Blocking viral entrance and replication and regulating humoral and cellular immunity in the uninfected population are the most often employed treatment approaches for viral infections. Unfortunately, no presently FDA-approved medicine can prevent or reduce SARS-CoV-2 access and reproduction. Until now, the most important element in disease severity has been the host's immune response activation or suppression. Several medicines have been adapted for COVID-19 patients, including arbidol, favipiravir, ribavirin, lopinavir, ritonavir, hydroxychloroquine, chloroquine, dexamethasone, and anti-inflammatory pharmaceutical drugs, such as tocilizumab, glucocorticoids, anakinra (IL-1β cytokine inhibition), and siltuximab (IL-6 cytokine inhibition). However, these synthetic medications and therapies have several side effects, including heart failure, permanent retinal damage in the case of hydroxyl-chloroquine, and liver destruction in the case of remdesivir. This review summarizes four strategies for fighting cytokine storms and immunomodulatory deficiency induced by COVID-19 using natural product therapy as a potential therapeutic measure to control cytokine storms.